PENERAPAN PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION MATERI BILANGAN PECAHAN DI SMP NEGERI 8 PONTIANAK - Ariyani, Ade Sisca; Jamiah, Yulis; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to know and describe the teacher’s class management, student’s learning activities, student’s respond and student’s outcomes in the implementation of cooperative learning with Group Investigation (GI) type in the operation of fraction topic at class VIIA SMPN 8 Pontianak. The research method is descriptive method. The research subject is students in class VIIA. Based on the data analysis that review four aspects, the results are: (1) the teacher’s class management categorized very good with average score 3,56; (2) student’s learning activities categorized active (72,35%); (3) student’s respond categorize positive with 6 student (25%) give a very positive respond and 18 student (75%) give a positive respond; and (4) student’s outcome is not reached classical completeness with only 41,67% of student can achieve the minimum completeness criteria. Because only three out of four aspects that achieved, the conclusion of this research is the implementation of cooperative learning with Group Investigation (GI) type less effective to apply in the operation of fraction topic at class VIIA SMPN 8 Pontianak. Key words: Cooperative learning, Group investigation, Effectiveness